Comparison of Maximal Oxygen Uptake and Post-Exercise Recovery Dynamics of Smoking and Non-Smoking Athletes - Manish Acharjee Shantunu; Rahul Dev Choudhury (CV Media Inti Teknologi, 2025)
Background of Study: Smoking has long been recognized as a risk factor for impaired cardiovascular and respiratory functions, yet its specific effects on athletic performance require further clarity. For athletes, maintaining high aerobic capacity and efficient recovery is essential for endurance, training adaptation, and competitive success. This study aimed to compare maximal oxygen and post-exercise recovery dynamics- VO2 Max, Heart Rate Recovery, Oxygen Saturation, and Breathing Frequency between smoking and non-smoking athletes.. Methods: A comparative cross-sectional design was employed with forty trained athletes aged 25–28 years, equally divided into smoking and non-smoking groups, each with at least four years of competitive training. Participants performed a graded treadmill exercise test followed by standardized recovery assessments under controlled laboratory conditions. Result: Findings revealed that non-smoking athletes achieved significantly higher maximal oxygen uptake, reflecting superior aerobic capacity. While differences in oxygen saturation, heart rate recovery, and breathing frequency were not statistically significant, smokers showed trends toward lower oxygen availability, slower cardiovascular recovery, and less efficient ventilatory adjustment. Conclusion: In conclusion, maximal oxygen uptake emerged as the most sensitive marker distinguishing smokers from non-smokers, underscoring the detrimental influence of tobacco use on endurance and recovery. These results emphasize the importance of discouraging smoking among athletes to safeguard physiological efficiency, support optimal training, & enhance long-term performance.